Preparation, characterisation and optimisation of cellulose nanoparticles from kenaf fibre and its application in polylactic acid reinforcement - Ketabchi, Mohammad-Reza (2018)
In this work, cellulose nanoparticles (CNP) were extracted from kenaf fibre and were used to reinforce natural rubber/polylactic acid biocomposites. The kenaf fibre was subjected for pretreatment by three different techniques namely, alkali treatment, bleaching, and sonication. A full factorial design of experiment was conducted in order to optimise the extraction process. The optimisation levels were adjusted according to single and full factorial studies of micro cellulose fibres. The extracted CNP was then structurally and morphologically characterised. The optimum nanoparticles were next employed to prepare the biocomposite. Prior to blending, processing parameters of polylactic acid (PLA) were optimised by a full factorial design of experiment including the main three compounding parameters i.e. speed, temperature, and duration. It was found that the alkali pre-treatment of the kenaf fibre had the most influencing effect to delignify kenaf fibre. An average cellulose particle diameter of ~100 nm was achieved when 0.2 g of NaOH/4 g of kenaf was used during alkali treatment, 5 ml of NaClO2/4 g of kenaf was employed during bleaching stage, and sonicated for 20 min. The compounding temperature was found to play a significant role; PLA samples prepared at higher temperatures than 180 °C displayed lower mechanical properties. Later, two single factorial compounding optimisations were carried for CNP/PLA and natural rubber/PLA nanocomposites preparations. Incorporation of 3 wt. % of CNP, and 10 wt. % of natural rubber was found adequate to enhance the elongation and impact resistance of PLA respectively. Therefore, the biocomposite was based on composition of 3 wt. % of CNP, and 10 wt. % of natural rubber hosted by PLA. The composition resulted in 1 %, 92 %, and 96 % improvements in tensile strength, young's modulus, and impact resistance of PLA respectively. It was observed that the biocomposite last for nearly 3072 h in soil and had a moderate biodegradation rate at ~0.15 % h-1. Moderate biodegradation of the biocomposite was found suitable to stabilise and control the fertiliser nutrients release in the soil. This finding has potential to be beneficial in view of environmental preservation and cost reduction for the production of kenaf fibre based biocomposites.